The structure of economic science : essays on methodology - Krupp, Sherman Roy (Englewood Cliffs, N.J. Prentice-Hall, 1966)
The book covers: Theory and dispute in economics; Mathematics and Observation in Economics; The Boundaries of Economic Theory; Value Premises in Economics.
Bibliographical footnotes.
rpm 05/10/2017
Loans
Keywords: Economics; Economic science; Economic - methodology